Comparison of Surgical Site Infection Rates Following Different Skin Preparation Techniques - Abbas Ali Raza, Laiba Tariq, Shabina, Azal Jodat, Asadullah Awan, Hamidullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Surgical site infections (SSIs) rank among the most frequent and easily preventable surgical complications. One of the Skin antisepsis performed before an operation, colloquially termed skin prep, is fundamental in reducing the possibility of infection. However, there is still confusion as to which antiseptic agent provides the best barrier. This study aimed to evaluate the effectiveness of chlorhexidine, povidone-iodine, and alcohol based solutions in the prevention of SSIs. Assess and analyze the rate of surgical site infections resulting from varying methods of skin preparation before surgery in a forward-looking group of surgical patients. Methods: An observational study was performed over a prospective 12 month period from January 2022 to January 2023 at the department of surgery, Mardan Medical Complex, Mardan. 79 patients undergoing various elective and emergency surgical procedures were enrolled. Participants received skin antisepsis using one of the following agents, chlorhexidine, povidone iodine, or alcohol based solution. The method of application and drying time were documented. SSIs were monitored for 30 days postoperatively and categorized as superficial, deep, or organ space infections. Infected wounds were microbiologically sampled for pathogen identification. Results: The overall SSI rate was 26.6%, with the lowest rate observed in the chlorhexidine group. Povidone-iodine and alcohol-based preparations showed higher infection rates in comparison. Superficial infections were the most common Staphylococcus aureus was the most commonly isolated pathogen. Selection of antiseptic, and within those, the wound’s grade in addition to the operation time impacted infection results. Conclusion: Chlorhexidine-based skin preparation was associated with a lower rate of SSIs compared to povidone-iodine and alcohol-based agents. These findings support the preferential use of chlorhexidine in surgical settings to improve postoperative outcomes. Keywords: Surgical site infection, Chlorhexidine, Povidone-iodine, Alcohol-based antiseptic, Skin preparation, Postoperative infection, Antiseptic efficacy